Bright AIE Nanoparticles with F127 Encapsulation for Deep‐Tissue Three‐Photon Intravital Brain Angiography. Issue 21 (10th August 2017) - Wang, Yalun; Han, Xiao; Xi, Wang; Li, Jinyu; Roe, Anna Wang; Lu, Ping; Qian, Jun
Abstract: Deep‐tissue imaging is of great significance to biological applications. In this paper, a deep‐red emissive luminogen 2, 3‐bis(4′‐(diphenylamino)‐[1, 1′‐biphenyl]‐4‐yl) fumaronitrile (TPATCN) with aggregation‐induced emission (AIE) feature is prepared. TPATCN molecules were then encapsulated within a polymeric matrix of Pluronic F‐127 to form nanoparticles (NPs). TPATCN NPs exhibit bright three‐photon fluorescence (3PF) in deep‐red region, together with high chemical stability, good photostability, and biocompatibility. They are further utilized for in vivo 3PF imaging of the brain vasculature of mice, under the excitation of a 1550 nm femtosecond laser. A vivid 3D reconstruction of the brain vasculature is then built with a penetration depth of 875 µm, which is the largest in ever reported 3PF imaging based on AIE NPs. After that, by collecting both of the 3PF and third‐harmonic generation signals, multichannel nonlinear optical imaging of the brain blood vessels is further realized. These results will be helpful to study the structures and functions of the brain in the future. Abstract : A type of aggregation‐induced emission luminogen 2, 3‐bis(4′‐(diphenylamino)‐[1, 1′‐biphenyl]‐4‐yl) fumaronitrile (TPATCN) with deep‐red emission and large Stokes shift is prepared. By the encapsulation of Pluronic F‐127, TPATCN nanoparticles (NPs) are obtained. They exhibit bright three‐photon fluorescence, good biocompatibility, and photostability. By intravenously injected with TPATCN NPs, the brain vasculature of a mouse is clearly and vividly imaged up to 875 µm.